2020
DOI: 10.1186/s42649-020-00035-6
|View full text |Cite
|
Sign up to set email alerts
|

Replacing critical point drying with a low-cost chemical drying provides comparable surface image quality of glandular trichomes from leaves of Millingtonia hortensis L. f. in scanning electron micrograph

Abstract: Sample preparation including dehydration and drying of samples is the most intricate part of scanning electron microscopy. Most current sample preparation protocols use critical-point drying with liquid carbon dioxide. Very few studies have reported samples that were dried using chemical reagents. In this study, we used hexamethyldisilazane, a chemical drying reagent, to prepare plant samples. As glandular trichomes are among the most fragile and sensitive surface structures found on plants, we used Millington… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 15 publications
0
12
1
Order By: Relevance
“…Apart from a long solvent exchange process, water can also be chemically converted to methanol and acetone by a fast reaction with 2,2-dimethoxypropane (DMP) at pH below 6 [67,86]. Since the removal of these solvents by evaporation still does not preserve the morphology well, they should be further exchanged with some water-immiscible liquids such as tetramethylsilane (Me 4 C, TMS) or hexamethyldisilazane (Me 3 -Si-NH-Si-Me 3 , HMDS) [85,[87][88][89][90][91]]. An even better option is to exchange them with CO 2 at supercritical conditions (above 31 • C and 7,3 •10 6 Pa), for which the surface tension vanishes [67,92].…”
Section: Dehydrationmentioning
confidence: 99%
“…Apart from a long solvent exchange process, water can also be chemically converted to methanol and acetone by a fast reaction with 2,2-dimethoxypropane (DMP) at pH below 6 [67,86]. Since the removal of these solvents by evaporation still does not preserve the morphology well, they should be further exchanged with some water-immiscible liquids such as tetramethylsilane (Me 4 C, TMS) or hexamethyldisilazane (Me 3 -Si-NH-Si-Me 3 , HMDS) [85,[87][88][89][90][91]]. An even better option is to exchange them with CO 2 at supercritical conditions (above 31 • C and 7,3 •10 6 Pa), for which the surface tension vanishes [67,92].…”
Section: Dehydrationmentioning
confidence: 99%
“…To avoid the collapse and shrinkage of E. coli cells, samples were carefully dehydrated following the protocol of biological sample preparations for scanning electron microscopy. 22 From topography imaging in Figure 4a, we observed that the E. coli cell has a rod shape of approximately 0.9 μm in width and 1.7 μm in length. For PFIR imaging, we first acquired dual-color images of E. coli simultaneously at 1744 and 1248 cm −1 shown in Figure 4c,d, respectively.…”
Section: ■ Resultsmentioning
confidence: 96%
“…To avoid the collapse and shrinkage of E. coli cells, samples were carefully dehydrated following the protocol of biological sample preparations for scanning electron microscopy . From topography imaging in Figure a, we observed that the E.…”
Section: Resultsmentioning
confidence: 99%
“…Following fixation, samples were rinsed with 1× PBS buffer for 10 min and subjected to a series of ethanol dehydration: 50%, 70%, 80%, and 100% ethanol, a 1:1 ethanol and hexamethyldisilazane (HMDS) solution, and HMDS absolute for 15–20 min for each step at room temperature. Samples then were laid on filter paper in mini glass petri dish with absolute HDMS overnight [ 26 , 27 ]. Samples were mounted on aluminum stubs with carbon adhesive tape and colloidal silver paint (Electron Microscopy Sciences, Hatboro, PA, USA) followed by sputter coating with gold-palladium using a Desk IV thin film coating system (Denton Vacuum, Moorestown, NJ, USA).…”
Section: Methodsmentioning
confidence: 99%